COVID‐19 and the uncertain future of HRM: Furlough, job retention and reform. (4th July 2021) - Stuart, Mark; Spencer, David A.; McLachlan, Christopher J.; Forde, Chris
Abstract: The article argues that job retention should be a central aim and practice of human resource management (HRM). Set against the global COVID‐19 crisis, theoretical insights are drawn from strategic HRM planning and the economics of 'labour hoarding' to consider the potential benefits of workforce furloughing. Furlough has been supported in the UK by the Coronavirus Job Retention Scheme, which represents a novel, but temporary, state‐led shift from the UK's market‐orientated restructuring regime. We argue that the withdrawal of state‐financed furlough may mean a quick return in UK firms to the management of redundancy. Yet, if the crisis is to generate any benefit it must create the conditions for a more collaborative HRM that delivers for workers as well as business, with job retention as a core priority. While change in this direction will mean confronting deep‐rooted challenges—such as job security, good work and worker voice—such change remains vital in creating better and healthier workplaces.